The effect of noise on digital phase locked loop circuit of second order - Muhamed Ibrahim Shujaa (Journal of Madenat Alelem University College, 2018)
This paper present a theoretical and experimental work of noise effect on the main performance measure of the second order zero crossing digital phase locked loop (ZDPLL). The loop error probability density function (P.D.F) satisfies the Chapman-kolomogrov equation. From this and the basic equation of approximate expression for the steady state phase error p.d.f. phase error variance and we obtained the loop noise bandwidth on matlab programme. The main measurement used in this paper is value of reliability, phase error variance, probability of correct locked and maximum phase jitter.